Gibran’s Opus The Prophet: Valuable Lessons for Better Life - Hassan, Abul Mobrur Mohammad Hamed (Mediterranean Journal of Social Sciences, 2012)
The Lebanese American Writer Khalil/Kahlil Gibran, who contributed to both Arabic and American literature was a literaryartist, philosopher, theologian, painter, sculptor and visual artist. His masterpiece, The Prophet, was acclaimed worldwide. Having beentranslated in more than twenty languages the book quenched the thirst for knowledge of millions of the knowledge seekers of the world.This book composed of 26 poetic essays was first published in 1923. This, the author's magnum opus, became especially popular duringthe 1960s with the American counterculture and New Age movements. Since it, The Prophet has never been out of print and remainsworld-renowned to this day.The book was the bestselling book of the twentieth century in the United States, second only to the Bible. Histhought provoking sayings in this outstanding piece of literature make us think about our life afresh. He strove to resolve cultural andhuman conflict transcending the barriers of East and West as few have done before. He became not only Gibran of Lebanon, but Gibranof America, indeed Gibran the voice of global consciousness: a voice which increasingly demands to be heard in the continuing Age ofAnxiety. This article draws a short biographical sketch of Gibran, deals with some inherent quality of the writings of Gibran andelucidates a few poetic essays of The Prophet so that the readers can have a glimpse of the great writer Kahlil Gibran.